Special Education and General Education Teacher Perceptions of Collaborative Teaching Responsibilities and Attitudes Towards an Inclusive Environment in Jordan - Alabdallat, Bassam; Alkhamra, Hatem; Alkhamra, Rana (Frontiers in Education, 2021)
The purpose of this study was to investigate how general and special education instructors perceive their collaborative teaching responsibilities and their attitudes toward inclusive environments. A self-administered questionnaire was distributed to 300 teachers in accordance with the social interdependence theory and cooperative learning conceptual framework. The survey was composed of two parts. The first section examined collaborative teaching duties for both instructors. It included 29 items and four categories (planning, instruction, evaluation, and behavior management). The second section included 15 items to assess attitudes toward inclusion. The study enrolled a total of 233 teachers (123 in special education and 110 in general education) with a response rate of 78%. The results showed that there was agreement between general and special education on only one of the four domains (instruction). Additionally, special education teachers expressed a more favorable attitude toward inclusion than did general education teachers. The current situation’s implications were explored with an emphasis on the necessity for additional shared practical activities among teachers.